Optimisation of vitamin B12 extraction from green edible seaweed (Ulva lactuca) by applying the central composite design - Darnis, Deny Susanti; Ruslan, Fatin Shazwani; Shukor, Muhammad Idham; Mohammad Noor, Normawaty; Aminudin, Nurul Iman; Bakhtiar, M. Taher; Khotib, Junaidi (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Vitamin B12, only found naturally in animal-based foods, is essential for brain functions and various chemical reactions in the human body. Insufficient vitamin B12 leads to vitamin B12 deficiency, common among strict vegetarians due to their limited intake of animal-based foods. Nevertheless, extensive studies have demonstrated that macroalgae, specifically the Ulva lactuca species, are rich in vitamin B12 and could be further exploited in future dietary applications. In the current study, the ideal extraction method of vitamin B12 from dried U. lactuca was developed and optimised to achieve the maximum vitamin B12 yield. The effects of several extraction parameters, including the solvent-to-solvent, methanol:water (MeOH:H2O), and solute-to-solvent ratios, and pH on the total vitamin B12 content were analysed through a two-level factorial and central com- posite design. The highest vitamin B12 content, particularly cyanocobalamin (CN-Cbl), was recov- ered through the ultrasonic-assisted extraction (UAE) of oven-dried U. lactuca at 3 g:60 mL of solute- to-solvent and 25:75% of MeOH to H2O ratios at pH 4. The extraction of CN-Cbl from oven-dried U. lactuca that employed the UAE method has elevated CN-Cbl content recovery compared to other extraction methods.